WCK 1152, WCK 1153: Discovery and structure activity relationship for the treatment of resistant pneumococcal and staphylococcal respiratory infections. (1st May 2022) - Bhawsar, Satish; Joshi, Sanjeev; Deshpande, Prasad; Yeole, Ravindra; Bhagwat, Sachin; Patel, Mahesh
Graphical abstract: Abstract: Novel antibacterial agents needed constantly to counter the ever emergent resistance development to commercially available drugs; one of the effective synthetic antibacterial classes is fluoroquinolone (FQ). This study includes structure activity relationship based design and synthesis of novel fluoroquinolone molecules active against resistant pathogens bearing mutations of DNA gyrase and/or topoisomerase IV which also express efflux pumps. Here, series of compounds were prepared by treating 1-cyclopropyl-6, 7-difluoro-8-methoxy-1, 4-dihydro-4-oxo-quinoline-3-carboxylic acid as a core with various 4-substituted-3, 3-dialkyl piperidines as side chains, through conventional synthetic approaches. Subsequently, antibacterial activities of these fluoroquinolones were examined against Streptococcus pneumoniae, SPN 5844 (Moxi resistant DNA gyrase and topo IV mutant) and SPN 706 (FQ efflux positive). The current manuscript covers >50 examples of fluoroquinolone NCEs, amongst 20 NCEs have shown MIC in the range of (0.4 to >6.25 μg/ml) for SPN 5844 and (0.1–12.5 μg/ml) for SPN 706 strains. During the course of this study; WCK 919, comprising two chiral isomers; WCK 1152 and WCK 1153 were emerged as lead among the different series synthesized. Advance studies suggested either WCK 1152 or WCK 1153 are the worthy candidates for further clinical developments for respiratory infections caused by resistant pneumococci and staphylococci . However, on the basis of in house preclinical work, WCK 1152 had been selected for phase-1 domestic clinical trials.